Antimicrobial Effect of Zataria multiflora and Rosemarinus officinalis on Antibiotic-resistant Staphylococcus aureus Strains Isolated from Food - MM Soltan Dallal; MH Yazdi; S Aghaamiri; SH Haghighat Khajavi; TP Abedi Mohtasab; F Amin Harati; M Gorbanzadeh Meshkani (Institue of Medicinal Plants, ACECR, 2014)
Background: Staphylococcus aureuse is one of the important pathogens which transmitted by food and has majority of habitant in human and animal community as a pathogen and normal flora. Antibiotic resistant among Staphylococcus aureuse strains is a global health challenge. Objective: Regarding to the different therapeutic and antimicrobial effect of Shirazi Zataria multiflora and Rosemarinus officonalis in present work the antibacterial effect of this extract and its synergistic effect with routine antibiotics was investigated. Methods: In this in vitro study the antimicrobial effect of Shirazi Zataria multiflora and Rosemarinus officonalis extract on methicillin resistant Staphylococcus aureus (MRSA) and other antibiotic resistant strains to tetracycline, erithromycine, trimethoprim, sulfamethoxazol, together with its MIC and MBC were determined. Also synergistic effect of these extracts with these antibiotics was investigated by paper disc method. Results: Shirazi zataria multiflora, had a significant antibacterial effect against MRSA, and other Staphylococcus aureus resistant strain to tetracycline, erithromycine, trimethoprim, and sulfametoxazol, isolated from food. Conclusion: Production of a suitable herbal medicine with few side effects will give rise to a promising outlook in the treatment of infections caused by antibiotic resistant strains of Staphylococcus aureus.